Method for recovering polymer from membrane

By mixing the lithium-ion battery separator with organic solvent and treating it with surfactant and deionized water, the problem of complex, high cost and secondary pollution in the prior art has been successfully solved, thus achieving efficient recovery of polymers and effective utilization of resources.

CN119684675AActive Publication Date: 2025-03-25CHINA AUTOMOTIVE BATTERY RES INST CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510205050.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

In the prior art, when recycling polymers in lithium-ion battery separators, the process is complex, expensive, and secondary pollution is present, making it difficult to achieve efficient utilization of resources.

Method used

The suspension is formed by mixing the broken separator with an organic solvent and sonicating it with ultrasonic treatment. The surfactant is then mixed with deionized water to form a mixed liquid. After mixing, the two are stirred, filtered and dried, the polymer is successfully recovered.

Benefits of technology

It realizes efficient recycling of polymers, with simple process, low cost, no secondary pollution, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684675A_ABST
    Figure CN119684675A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries. The invention provides a method for recovering a polymer from a diaphragm, and the method comprises the following steps: crushing the diaphragm, mixing the crushed diaphragm with an organic solvent, and carrying out ultrasonic treatment to obtain a suspension; a surfactant and deionized water are mixed to obtain a mixed solution, the molar concentration of the surfactant in the mixed solution is 1 mmol / L-10 mmol / L, and the surfactant comprises at least one of lauryl sodium sulfate, sodium dodecyl benzene sulfonate and alkyl polyoxypropylene ether sodium sulfate; and mixing the suspension and the mixed solution, stirring, filtering, collecting filter residues, and drying to obtain the polymer. According to the method, the ceramic particles are solubilized in the deionized water through the surfactant, separation of the ceramic particles and the polymer-based membrane is achieved, so that the polymer-based membrane is efficiently recycled, the method is simple, the cost is low, secondary pollution is avoided in the recycling process, and industrial production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular, to a method for recovering polymers from separators. Background Art

[0002] As a new type of energy storage device, lithium-ion batteries have been widely used in many fields such as mobile phones, laptops, digital cameras, etc. With the large-scale scrapping of lithium-ion batteries, how to recycle the polymers in the separator materials of waste lithium-ion batteries has become an urgent problem to be solved.

[0003] At present, the main treatment methods for waste lithium-ion battery diaphragm materials are landfill or incineration, which not only causes a huge waste of resources, but also causes serious pollution to the environment. Although there are some methods to try to recycle and reuse diaphragm materials, there are many shortcomings, such as complex processes, high costs, and serious secondary pollution. Therefore, it is urgent to develop a simple, efficient, low-cost, and non-secondary pollution method to recover polymers from waste lithium-ion battery coated diaphragms and realize the resource utilization of solid waste. Summary of the invention

[0004] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0005] In a first aspect, the present application provides a method for recovering a polymer from a diaphragm, the method comprising: crushing the diaphragm and mixing it with an organic solvent, and ultrasonically treating it to obtain a suspension; mixing a surfactant with deionized water to obtain a mixed solution, wherein the molar concentration of the surfactant in the mixed solution is 1 mmol / L-10 mmol / L, and the surfactant comprises at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium alkyl polyoxypropylene ether sulfate; mixing the suspension and the mixed solution, stirring, filtering, collecting the filter residue and drying it to obtain a polymer.

[0006] The method for recovering polymers from a diaphragm proposed in the present application uses a surfactant to solubilize ceramic particles in deionized water to achieve separation of the ceramic particles and the polymer-based membrane, thereby efficiently recovering the polymer-based membrane. The method is simple, low-cost, and has no secondary pollution during the recovery process, making it easy to industrialize.

[0007] According to some embodiments of the present application, the surfactant includes C n H 2n+1 O(CH2OCHCH3) p SO3Na, wherein n is an integer of 8 to 16, and p is an integer of 3 to 12. Thus, the solubilization effect on ceramic particles is improved.

[0008] According to some embodiments of the present application, the molar concentration of the surfactant in the mixed solution is 3 mmol / L-8 mmol / L, thereby improving the solubilization effect on the ceramic particles.

[0009] According to some embodiments of the present application, the power of the ultrasonic treatment is 500W-1000W, and the frequency of the ultrasonic treatment is 100kHz-300kHz, thereby improving the dissolution effect of the binder in the organic solvent.

[0010] According to some embodiments of the present application, the area of ​​the single piece of the diaphragm after being broken is 0.5 cm 2 -10cm 2 Thus, the contact area between the separator and the organic solvent is increased, and the dissolution effect of the binder in the organic solvent is improved.

[0011] According to some embodiments of the present application, the organic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylamide, dimethyl sulfoxide, tetrahydrofuran, and acetone.

[0012] According to some embodiments of the present application, the mass ratio of the membrane to the organic solvent in the suspension is 1:(5-10), thereby fully dissolving the polymer in the membrane.

[0013] According to some embodiments of the present application, when the suspension and the mixed liquid are mixed, the volume ratio of the suspension and the mixed liquid is 1:(0.7-1.3).

[0014] According to some embodiments of the present application, the drying temperature is 80° C.-150° C. Thus, the residual organic solvent in the polymer is reduced.

[0015] According to some embodiments of the present application, the diaphragm includes any one of a polyethylene diaphragm, a polypropylene diaphragm, a polyethylene-polypropylene double-layer diaphragm, and a polyethylene-polypropylene-polyethylene three-layer diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 A schematic flow chart of a method for recovering a polymer from a membrane according to an embodiment of the present application is shown. DETAILED DESCRIPTION

[0017] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0018] In a first aspect, the present application provides a method for recovering a polymer from a diaphragm, the method comprising: disassembling a battery to obtain a diaphragm, crushing the diaphragm and mixing it with an organic solvent, and ultrasonically treating it to obtain a suspension; mixing a surfactant with deionized water to obtain a mixed solution, wherein the molar concentration of the surfactant in the mixed solution is 1 mmol / L-10 mmol / L, and the surfactant comprises at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium alkyl polyoxypropylene ether sulfate; mixing the suspension and the mixed solution, stirring, filtering, collecting the filter residue and drying it to obtain a polymer.

[0019] The diaphragm includes a polymer base film and a functional coating located on at least one side of the polymer base film, and the functional coating mainly includes a binder and ceramic particles. The method for recovering polymers from the diaphragm proposed in the present application is to mix the broken diaphragm with an organic solvent, and the organic solvent can dissolve the binder in the functional layer, so that the ceramic particles in the functional layer are separated from the polymer base film. After adding an aqueous solution containing a surfactant, the surfactant is adsorbed on the surface of the ceramic particles by electrostatic action to form a double-layer adsorption micelle, which shows surface solubilization or adsorption solubilization characteristics for the ceramic particles, so that the ceramic particles are solubilized in deionized water. The organic solvent and deionized water bidirectional solvent can further enhance this separation effect, and the solvent and the ceramic particles in the solvent are removed by filtering, and the filter residue is collected. The composition of the filter residue is the polymer base film, and the residual organic solvent is removed by drying, and the polymer base film can be efficiently recovered. The method proposed in the present application has a simple process, is easy to operate, does not require complex equipment and processes, and is easy to industrialize. The surfactant used is low in cost, which reduces the recovery cost, and there is no secondary pollution in the recovery process.

[0020] The method proposed in this application is described in detail below. Figure 1 , the method comprising: S10: Disassembling the battery to obtain a separator, crushing the separator and mixing it with an organic solvent, and ultrasonically treating the separator to obtain a suspension In this step, after disassembling the battery to obtain the diaphragm, the diaphragm is crushed by mechanical crushing or freezing crushing, the crushed diaphragm fragments are screened, the screened fragments are mixed with an organic solvent, heated and stirred, and ultrasonic treatment is used to assist dispersion to obtain a suspension. The heating, stirring and ultrasonic treatment are used to fully dissolve the binder in the functional layer, thereby causing the ceramic particles to fall off from the diaphragm into the solvent.

[0021] According to some embodiments of the present application, the power of the ultrasonic treatment is 500W-1000W, and the frequency of the ultrasonic treatment is 100kHz-300kHz, thereby improving the dissolution effect of the binder in the organic solvent and fully separating the ceramic particles from the polymer base film.

[0022] As an example, the power of the ultrasonic treatment can be 500 W, 600 W, 700 W, 800 W, 900 W, 1000 W, etc., or can be a range consisting of any of the above numerical values.

[0023] As an example, the frequency of the ultrasonic treatment can be 100 kHz, 150 kHz, 200 kHz, 250 kHz, 300 kHz, etc., or can be a range consisting of any of the above values.

[0024] According to some embodiments of the present application, the area of ​​the single piece of the diaphragm after being broken is 0.5 cm 2 -10cm 2 For example, it can be 0.5 cm 2 , 1cm 2 , 3cm 2 , 5cm 2 、7cm 2 、9cm 2 , 10cm 2 By breaking the larger diaphragm into smaller diaphragm fragments, the diaphragm fragments are fully contacted with the organic solvent, the wetting effect of the organic solvent on the diaphragm fragments is improved, and the binder in the functional layer of the diaphragm fragments is fully dissolved.

[0025] According to some embodiments of the present application, the organic solvent includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylacetamide, N,N-dimethylamide, dimethyl sulfoxide, tetrahydrofuran, and acetone.

[0026] According to some embodiments of the present application, the organic solvent includes at least one of N-methylpyrrolidone, tetrahydrofuran, and acetone.

[0027] According to some embodiments of the present application, the mass ratio of the membrane to the organic solvent in the suspension may be 1:(5-10). For example, it may be 1:5, 1:7, 1:9, 1:10, etc., or may be a range of any of the above values. Thus, the binder in the membrane functional layer is fully dissolved.

[0028] S20: Mixing a surfactant with deionized water to obtain a mixed solution, wherein the molar concentration of the surfactant in the mixed solution is 1 mmol / L-10 mmol / L, and the surfactant includes at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium alkyl polyoxypropylene ether sulfate. In this step, the surfactant is mixed with deionized water, and the molar concentration of the surfactant can be 1mmol / L, 3mmol / L, 5mmol / L, 7mmol / L, 9mmol / L, 10mmol / L, etc., or can be a range composed of any of the above numerical values. Thus, by making the concentration of the surfactant in the above range, the solubilization effect on the ceramic particles is improved. According to some embodiments of the present application, the molar concentration of the surfactant can be 3mmol / L-8mmol / L.

[0029] According to some embodiments of the present application, the surfactant may include C n H 2n+1 O(CH2OCHCH3) p SO3Na, wherein n is an integer of 8-16, and p is an integer of 3-12.

[0030] Linking group in surfactant - (CH2OCHCH3) p - It has a biphasic affinity, which can increase the adsorption area of ​​the surfactant on the surface of the ceramic particles, forming a double adsorption layer on the surface of the ceramic particles, thereby having a stronger adsorption and solubilization ability, making the separation of the ceramic particles and the polymer-based membrane more thorough, thereby improving the recovery rate of the polymer-based membrane.

[0031] As an example, n may be 8, 10, 12, 14, 16, etc., or may be a range consisting of any of the above values.

[0032] As an example, p may be 3, 5, 7, 9, 11, 12, etc., or may be a range consisting of any of the above values.

[0033] According to some embodiments of the present application, the surfactant may be C8H 17 O-(CH2CHCH3O)6SO3Na、C 10 H 21 One or both of O-(CH2CHCH3O)8SO3Na.

[0034] S30: mixing the suspension and the mixed solution, stirring, filtering, collecting the filter residue and drying it to obtain a polymer In this step, after the suspension and the mixed liquid are mixed, stirring is continued for 3h-6h, the mixed liquid is filtered by ultrasonic vibration, the screen is 200 mesh, and the collected filter residue is rinsed with deionized water. The filter residue is placed under vacuum conditions and dried to obtain a polymer-based membrane.

[0035] According to some embodiments of the present application, when the suspension and the mixed solution are mixed, the volume ratio of the suspension and the mixed solution is 1:(0.7-1.3). Thus, the ceramic particles are solubilized in deionized water, thereby improving the recovery rate of the polymer-based membrane.

[0036] According to some embodiments of the present application, the volume ratio of the suspension to the mixed liquid is 1:1.

[0037] According to some embodiments of the present application, the drying temperature is 80° C.-150° C. For example, it can be 80° C., 100° C., 130° C., 150° C., etc., or can be a range of any of the above values. Thus, the residual organic solvent in the polymer-based film is reduced.

[0038] According to some embodiments of the present application, the vacuum degree of the vacuum device is -0.080 MPa (G) to -0.090 MPa (G).

[0039] According to some embodiments of the present application, the drying time is 3h-7h.

[0040] According to some embodiments of the present application, the diaphragm includes any one of a polyethylene diaphragm, a polypropylene diaphragm, a polyethylene-polypropylene double-layer diaphragm, and a polyethylene-polypropylene-polyethylene three-layer diaphragm.

[0041] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0042] Example 1 1. Use mechanical crushing to crush the waste lithium-ion battery coated diaphragm, screen the broken diaphragm fragments, and control the single piece area to 1cm 2 ~5cm 2 ; 2. The membrane fragments (100 g) were mixed with N-methylpyrrolidone (800 g) to obtain a suspension, and stirred at 100 °C for 5 h while using ultrasonic assisted dispersion with an ultrasonic power of 800 W and an ultrasonic frequency of 200 kHz; 3. Add alkyl polyoxypropylene ether sodium sulfate surfactant to deionized water to obtain a mixed solution, C8H 17 O-(CH2CHCH3O)6SO3Na (n=8, p=6), the concentration is controlled at 5mmol / L, the volume ratio of deionized water to organic solvent is 1:1, stirring is continued for 5h, and then the material is filtered by ultrasonic vibration, the screen is 200 mesh, and the filter residue is collected after rinsing three times with deionized water; the filter residue is placed in a vacuum environment with a vacuum degree of -0.080~-0.090MPa, and dried at 120°C for 5h to obtain a polymer base film recycled material with a weight of 85.3g.

[0043] To calculate the recovery rate, the filtrate was concentrated by evaporation to collect the solid residue, which was washed three times with deionized water to remove the surfactant added in step 3. The solid residue was calcined at 1000°C for 5h in an air atmosphere to remove organic residues, and pure ceramic powder was obtained after calcination, weighing 11.6g.

[0044] The calculated recovery efficiency is 85.3 / (100-11.6) *100%= 96.5%.

[0045] Example 2 The method for recovering the polymer base film from the diaphragm is the same as that in Example 1, except that the organic solvent is tetrahydrofuran.

[0046] Example 3 The method for recovering the polymer base film from the diaphragm is the same as in Example 1, except that the surfactant is C 10 H 21 O-(CH2CHCH3O)8SO3Na (n=10, p=8).

[0047] Example 4 The method for recovering the polymer-based film from the diaphragm is the same as that in Example 1, except that the concentration of the surfactant in the mixed solution is 3 mmol / L.

[0048] Example 5 The method for recovering the polymer-based film from the diaphragm is the same as that in Example 1, except that the concentration of the surfactant in the mixed solution is 8 mmol / L.

[0049] Example 6 The method for recovering the polymer-based film from the diaphragm is the same as that in Example 1, except that the concentration of the surfactant in the mixed solution is 1 mmol / L.

[0050] Example 7 The method for recovering the polymer-based film from the diaphragm is the same as that in Example 1, except that the concentration of the surfactant in the mixed solution is 10 mmol / L.

[0051] Example 8 The method for recovering the polymer-based film from the diaphragm is the same as that in Example 1, except that the surfactant is sodium dodecyl sulfate.

[0052] Example 9 The method for recovering the polymer-based film from the diaphragm is the same as that in Example 1, except that the surfactant is sodium dodecylbenzene sulfonate.

[0053] Comparative Example 1 The method for recovering the polymer base film from the diaphragm is the same as that in Example 1, except that: 3. Mix deionized water with the suspension, the volume ratio of deionized water to organic solvent is 1:1, continue stirring for 5 hours, and then filter the material by ultrasonic vibration. The sieve is 200 mesh. After rinsing three times with deionized water, collect the filter residue; place the filter residue in a vacuum environment with a vacuum degree of -0.080~-0.090MPa, and dry it at 120°C for 5 hours to obtain the polymer base film recycled material.

[0054] Comparative Example 2 1. Use mechanical crushing to crush the waste lithium-ion battery coated diaphragm, screen the broken diaphragm fragments, and control the single piece area to 1cm 2 ~5cm 2 ; 2. Mix the diaphragm fragments (100 g) with N-methylpyrrolidone (800 g) to obtain a suspension, stir at 100°C for 5 h, and use ultrasonic assisted dispersion at a power of 800 W and a frequency of 200 kHz. Then filter the material by ultrasonic vibration, using a 200-mesh screen, rinse three times with deionized water, and collect the filter residue; place the filter residue in a vacuum environment with a vacuum degree of -0.080~-0.090 MPa, and dry at 120°C for 5 h to obtain a polymer-based membrane recycled material.

[0055] Comparative Example 3 The method for recovering the polymer-based film from the diaphragm is the same as that in Example 1, except that the surfactant is hexadecyltrimethylammonium bromide.

[0056] Comparative Example 4 The method for recovering the polymer-based film from the diaphragm is the same as that in Example 1, except that the concentration of the surfactant in the mixed solution is 12 mmol / L.

[0057] The recovery rates of the polymers in Examples 1 to 9 and Comparative Examples 1 to 4 are shown in Table 1.

[0058] Table 1

[0059] It can be seen from the comparison between Examples 1 to 9 and Comparative Examples 1 to 4 that, in the process of recovering the polymer-based film in the diaphragm, by adding a specific type and a specific content of surfactant, the ceramic particles in the diaphragm have a solubilizing function, so that the ceramic particles are completely separated from the polymer-based film, and the polymer-based film is efficiently recovered.

[0060] It can be seen from the comparison between Examples 4 to 7 and Comparative Example 4 that if the concentration of the surfactant is too high, the surfactant in the solution is more likely to self-aggregate to form micelles, and the number of free surfactant molecules is reduced, resulting in a decrease in the amount of adsorption on the surface of the ceramic particles, and thus the dispersion ability is deteriorated. In addition, when the concentration of the surfactant is too high, the viscosity of the solution increases, the separation efficiency of mechanical stirring is reduced, the separation effect is also affected, and the recovery rate of the polymer-based membrane is reduced.

[0061] It can be seen from the comparison between Examples 1 to 9 and Comparative Example 3 that the use of anionic surfactants has a better solubilization effect on ceramic particles and can improve the recovery rate of the polymer-based membrane.

[0062] It can be seen from the comparison between Examples 1 to 9 and Comparative Examples 1 and 2 that the ceramic particles in the diaphragm cannot be completely washed away by only using deionized water to clean the suspension containing the diaphragm fragments, and the recovery rate of the polymer-based membrane is low.

[0063] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0064] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for recovering a polymer from a diaphragm, characterized in that: include: The membrane is crushed and mixed with an organic solvent, and subjected to ultrasonic treatment to obtain a suspension; Mixing a surfactant with deionized water to obtain a mixed solution, wherein the molar concentration of the surfactant in the mixed solution is 1 mmol / L-10 mmol / L, and the surfactant includes at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium alkyl polyoxypropylene ether sulfate; The suspension and the mixed solution are mixed, stirred, filtered, and the filter residue is collected and dried to obtain a polymer.

2. The method according to claim 1, characterized in that: The surfactant includes C n H 2n+1 O(CH2OCHCH3) p SO3Na, wherein n is an integer of 8-16, and p is an integer of 3-12.

3. The method according to claim 1 or 2, characterized in that: The molar concentration of the surfactant in the mixed solution is 3mmol / L-8mmol / L.

4. The method according to claim 1 or 2, characterized in that: The power of the ultrasonic treatment is 500W-1000W, and the frequency of the ultrasonic treatment is 100kHz-300kHz.

5. The method according to claim 1 or 2, characterized in that: The area of ​​the single piece of the diaphragm after breaking is 0.5cm 2 -10cm 2 .

6. The method according to claim 1 or 2, characterized in that: The organic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylamide, dimethyl sulfoxide, tetrahydrofuran and acetone.

7. The method according to claim 1 or 2, characterized in that: The mass ratio of the membrane to the organic solvent in the suspension is 1:(5-10).

8. The method according to claim 1 or 2, characterized in that: When the suspension and the mixed liquid are mixed, the volume ratio of the suspension and the mixed liquid is 1:(0.7-1.3).

9. The method according to claim 1 or 2, characterized in that: The drying temperature is 80°C-150°C.

10. The method according to claim 1 or 2, characterized in that: The diaphragm includes any one of a polyethylene diaphragm, a polypropylene diaphragm, a polyethylene-polypropylene double-layer diaphragm, and a polyethylene-polypropylene-polyethylene three-layer diaphragm.

Citation Information

Patent Citations

  • Combined treatment method of waste lithium ion battery negative electrode and diaphragm

    CN110444830A

  • Method for recovering lithium carbonate from waste ternary lithium battery

    CN118320786A

  • Method for recovering mold release film

    JP2002265665A

  • Preparation method of support membrane for recovering hydrocarbon and support membrane prepared therefrom

    KR1020100013617A

  • Recycling system for spent lithium ion battery pack

    KR102499905B1